Downtown Fresno Nuclear Freeze March to and Vigil in Courthouse Breezeway - Watkins, Howard::::::::: (1982)
, Jacqueline Pillar, Connie Petersen, Louise Erickson holding Women's International League for Peace and Freedom banner